LEGAL ISSUES RELATING TO PATCHWORK FAMILIES: A NORMATIVE ANALYSIS AND THE LEGAL STATUS OF THE CHILDREN - Skłodowski, Dariusz (Zeszyty Prawnicze, 2025)
This article examines the legal complexities surrounding patchwork families, focusing on the rights of children within such structures. A patchwork family, defined as a family formed by the remarriage or cohabitation of one or both parents with new partners, often involves multiple parental figures and step-siblings. The article explores legal challenges related to parental authority, maintenance rights, and arrangements for a child’s contact with its parents, especially in jurisdictions where traditional family structures are dominant. Key issues discussed include the child’s legal status concerning biological parents and stepparents, the legal recognition of the child’s relationship with non-biological family members, and the potential conflicts that may arise when there is a gap between legal recognition and social bonds. The article also considers the implications for children’s rights in terms of guardianship, support, and the protection of their welfare in a patchwork family.